Strategic brand management :Building, measuring and managing brand equity /Kevin Lane Keller, Vanitha Swaminathan. - Keller, Kevin Lane.
For students, managers and senior executives studying Brand Management. Keller provides insights into how to create profitable brand strategies by building, measuring, and managing brand equity.